Pan-Africanism as a laughing matter: (Funny) expressions of African identity on Twitter. (1st June 2019) - Cheruiyot, David; Uppal, Charu
Pan-Africanism, a concept that attempts to capture the essence of being an African, needs to be reconsidered in the age of social media. In this article, we examine how Twitter users negotiate the question of African identity through humorous hashtagdriven conversations. We specifically question whether a new kind of Pan-Africanism is emerging on Africa's Twitterverse through the use of a popular hashtag in 2015, #IfAfricaWasABar. In our analysis of tweets linked to #IfAfricaWasABar, we conclude that Twitter provides temporary solidarity by engaging users in humorous exchanges regarding the sociocultural, political and economic issues that define the African continental condition today.